A Letter and Encouragement: Does Information Increase Post-Secondary Enrollment of UI Recipients? - Andrew Christopher Barr; Sarah E. Turner (Center for Economic Studies and ifo Institute (CESifo), 2017)
For individuals who experience job loss, enrollment in post-secondary programs may provide an opportunity to improve future employment outcomes. However, decisions to enroll may be hampered by insufficient information about the benefits and costs and the necessary steps and assistance available to facilitate such investments. Using variation in the dissemination and timing of letters sent to UI recipients containing this information, we find that individuals sent the information are 40% more likely to enroll. These findings suggest that well-coordinated information interventions delivered with institutional support may be more effective than raising the generosity of existing government programs in increasing participation.
Keywords: 330